Kinetics of Moisture Loss and Oil Absorption of Pork Rinds during Deep-Fat, Microwave-Assisted and Vacuum Frying - Lin, Hong-Ting Victor; Chan, Der-Sheng; Huang, Yu-Hsiang; Sung, Wen-Chieh (Foods, 2021)
The fat content of fried pork rinds is high, and alternative frying helps reduce the oil content and maintain their texture and taste. Different frying methods such as microwave-assisted, traditional deep frying and vacuum frying on the breaking force, color, microstructure, water loss and oil absorption attributes of fried pork rinds were evaluated in this study. The fat content of microwave-assisted and vacuum-fried pork rinds was lower (24.2 g/100 g dry weight basis (db) and 17.1 g/100 g db, respectively) than that (35.6 g/100 g db) of traditional deep-fat frying. Non-uniform, holy and irregular surface microstructures were obtained by vacuum frying due to rapid mass transfer at low pressure. The first-order kinetic models of water loss and oil absorption of traditional and microwave-assisted frying of pork rinds were established. Microwave frying caused a faster moisture loss rate, shorter frying time and lower pork rind oil content, makes it an attractive substitute for traditional deep-fat frying.